Hubungan Konsumsi Natrium/Garam dengan Status Hipertensi: Studi Cross Sectional di Kota Makassar - Firman, Firman (Multidisciplinary Journal of Education , Economic and Culture, 2024)
Hypertension disease contributes 7% to the global burden of disease and causes 17 million deaths per year. The prevalence of hypertension (age ? 18 years) in the world is 22 with rates based on gender higher in men at 25.3% and in women 24.2%. This study aims to determine the relationship of sodium / salt consumption with the incidence of hypertension of productive age in the Tamalanrea Jaya Health Center working area in 2019. The type of research used was analytic observational with a cross sectional study design. The population in this study were all hypertensive patients of productive age (15-64) years who were recorded in the Tamalanrea Jaya Health Center register book in the time span starting in January to September 2019, which amounted to 215 people. The sampling technique used was simple random sampling with a sample size of 140 patients. Data were analyzed using SPSS with the Chi-square test. The results showed that there was a relationship between sodium / salt consumption (p = 0.000) on the incidence of hypertension with p value ?0.05